REPRODUKSI KEBERADAAN PEDAGANG KAKI LIMA (PKL) MELALUI INTERAKSI ANTAR KELOMPOK KEPENTINGAN - Dondick Wicaksono Wiroto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
Informal sector which wish to study through this research are sidewalk vendors in the informal sector (street vendors or PKL). The exitence of street vendors becomes a problem for local governments in Indonesia and a challenge for city governments to make re-arrangement of street vendors. However, to avoid deification to the role of government, it is necessary to examine practices in the interaction between interest groups that may be involved in situations to support and not support the street vendors, so that street vendors always able to reproduce their existence. Conception of practical and discursive consciousness and power practice which is derived from Giddens structuration theory will be used to explain that PKL resistance arises not only because of the structural pressures but also because there is interaction between the actors of interest groups.